Antibacterial Potential of Rhinacanthus Nasutus Leaf Extract Against Escherichia Coli and Streptococcus Pneumoniae in Vitro - Betty Fitriyasti; Irfan Maulana; Adelia Fitri; Nurhuda; Rifkind Malik; Muhammad Rezki Syahputra (Journal of Public Health Indonesian, 2026)
Antibiotic resistance is a growing global health problem that impacts the effectiveness of infection therapy (World Health Organization [WHO], 2024). Therefore, safe and effective antibacterial alternatives are needed, including those derived from natural ingredients such as Rhinacanthus nasutus (L.) Kurz, which is known to contain bioactive compounds. This study aimed to evaluate the antibacterial activity of ethanolic extract of Rhinacanthus nasutus leaves against Escherichia coli and Streptococcus pneumoniae in vitro. The method used was well diffusion on Mueller–Hinton Agar media with varying extract concentrations of 15%, 30%, and 60%. Ciprofloxacin was used as a positive control and distilled water as a negative control. Antibacterial activity was measured based on the diameter of the inhibition zone after 24 hours of incubation at 37°C and analyzed using one-way ANOVA. The results showed that the extract was able to inhibit the growth of both test bacteria, with an increase in the diameter of the inhibition zone with increasing concentration. Statistical analysis showed a significant difference between treatment groups (p < 0.05). However, the inhibitory power of the extract was still lower than that of the positive control. These findings indicate that Rhinacanthus nasutus has the potential to be developed as a natural antibacterial, but further research is needed to optimize its effectiveness and safety.